Atomic structure and polarity compensation of BaTiO3 (1 1 1) surface. (11th February 2015) - Li, Yueliang; Yu, Rong; Shi, Tao; Liao, Zhenyu; Song, Dongsheng; Zhou, Huihua; Cheng, Zhiying; Zhu, Jing
Abstract: Surfaces of perovskite-type oxides have been attracting increasing interest for their primary importance in various potential applications such as multiferroic thin films, interface electronics and catalysis. However, the (1 1 1) surface of BaTiO3, the most typical ferroelectric, is far from well understood. In this work, the atomic structure and polarity compensation of BaTiO3 (1 1 1) surface have been investigated combining aberration-corrected transmission electron microscopy and first-principle calculations. Depending on the density of oxygen vacancies, the surface shows different degrees of atomic relaxation and electronic charge transfer, which compensates the surface polarity together with the ionic charges associated with the oxygen vacancies. The atomic relaxation and charge transfer would have a direct impact on the ferroelectric and catalytic properties of low-dimensional BaTiO3 .